Evaluation of DNA adduct damage using G-quadruplex-based DNAzyme - Yi Xiao; Haomin Yi; Jingzhi Zhu; Suhua Chen; Guofang Wang; Yilong Liao; Yuanyuan Lei; Liyin Chen; Xingcai Zhang; Fangfu Ye (Bioactive Materials, 2023)
Toxicity assessment is a major problem in pharmaceutical candidates and industry chemicals development. However, due to the lack of practical analytical methods for DNA adduct analysis, the safety evaluation of drug and industry chemicals was severely limited. Here, we develop a DNAzyme-based method to detect DNA adduct damage for toxicity assessment of drugs and chemicals. Among 18 structural variants of G4 DNAzyme, EA2 DNAzyme exhibits an obvious DNA damaging effect of styrene oxide (SO) due to its unstable structure. The covalent binding of SO to DNAzyme disrupts the Hoogsteen hydrogen bonding sites of G-plane guanines and affects the formation of the G4 quadruplex. DNA damage chemicals reduce the peroxidase activity of the G4 DNAzyme to monitor the DNA adduct damage by disrupting the structural integrity of the G4 DNAzyme. Our method for genotoxic assessment of pharmaceutical candidates and industrial chemicals can elucidate the complex chemical pathways leading to toxicity, predict toxic effects of chemicals, and evaluate possible risks to human health.